Theoretical Bases Of The Organization Of Accounting On Farms - Mamanazarov T-Andijan (Genius Journals, 2021)
In this article, the author discusses the theoretical basis for the organization of accounting in diversified farms operating in the Republic of Uzbekistan.
Keywords: Farm; Accounting; Assets; Liabilities